Scholarly misconduct : law, regulation, and practice - Freckelton, Ian R. (Oxford University Press, 2016)
This book examines scholarly misconduct in all its forms, from research fraud to forensic misconduct. Taking each type of misconduct in turn, the book details and analyses notorious cases, and court and disciplinary tribunal case law from around the world, looking specifically at the legal and regulatory responses that were evoked in each instance.